Spiral of Talk - Luodan Pan; Arthur Ituassu (Revista Contracampo, 2024)
This political communication research analyzes the impact of digital media on public opinion in the context of the 2019 Hong Kong protests. It is a qualitative and interpretive study that observes how people participate in political discussions through social media. The survey aims to investigate the opinions and expressions surrounding the proposed theme, using a case study as a research strategy and adopting methods such as framing and qualitative content analysis. We questioned whether there was a spiral of silence on social media concerning the protests. To answer that, we manually analyzed 76 posts on the Facebook website of the South China Morning Post and 2,000 public comments. The theory of the spiral of silence points out that people retain their opinions when they think the climate of opinion is contrary to them, with silence increasing over time. However, this research on Facebook about the 2019 Hong Kong protests shows that a minority of opinion holders retained to speak. Besides that, people with minority views began to express their positions with time, interrupting the spiral. The research aimed to advance the ambiance for public political participation on social media by studying the media environment and media content. This unique background in the Hong Kong Anti-Extradition Law Amendment Bill movement has innovative significance, enriching empirical research on Eastern countries and providing new ideas for investigating non-campaign political participation in social media.